Sentencing Disparity and the Reformulation of Rehabilitation Policy for Narcotics Users under Law Number 35 of 2009 and the Indonesian National Criminal Code - Mardana Rifta Oktaviana; Ali Masyhar; Cahya Wulandari (Al-Risalah, 2026)
Drug abuse in Indonesia continues to generate complex legal and public health problems due to the inconsistency between punitive narcotics law enforcement and recovery-oriented rehabilitation policies. Although Law Number 35 of 2009 concerning Narcotics recognizes rehabilitation through Articles 54, 103, and 127, the implementation of these provisions remains ineffective because the law simultaneously criminalizes narcotics users while providing facultative rehabilitation measures. The phrase “may” in Article 103 creates excessive judicial discretion, resulting in sentencing disparities, inconsistent rehabilitation practices, and the continued dominance of imprisonment for narcotics users. This condition reflects a normative conflict between punitive criminalization under the Narcotics Law and the rehabilitative measures paradigm introduced by Law Number 1 of 2023 concerning the Indonesian National Criminal Code. This study aims to analyze the doctrinal weaknesses of rehabilitation regulation for narcotics users and formulate an integrated rehabilitation model within the national criminal law system. This research employs normative legal research using statutory, conceptual, and case approaches through qualitative legal analysis of legislation, court decisions, and criminal law doctrines. The study finds that the primary weakness of the current rehabilitation policy lies in the ambiguity of legal subject classification, the absence of standardized assessment mechanisms, and the facultative nature of rehabilitation norms. This study proposes a reformulation model in the form of mandatory conditional rehabilitation for narcotics users and addicts proven to consume narcotics for personal use and not involved in trafficking networks. The reformulation should systematically integrate rehabilitation provisions in the Narcotics Law with rehabilitative measures under Articles 103 and 105 of the Indonesian National Criminal Code to establish a more proportional, health-based, and restorative criminal justice system. This model contributes to contemporary Indonesian criminal law reform by strengthening therapeutic jurisprudence and public health criminal policy approaches in narcotics law enforcement.